Adsorption of reactive orange 4 on sesame stalks. modeling, kinetics and equilibrium - Tanyildizi, M. Şaban; Demirci, Yavuz (Wroclaw University of Science and Technology, 2017)
Placket-Burman design (PBD) and central composite design (CCD) were employed to study the adsorption of Reactive Orange 4 (RO4) on sesame stalk. In the study conducted with the PBD, a total of seven parameters (initial dye concentration, initial pH of solution, temperature, amount of adsorbent, particle size, contact time, and shaking speed) were studied, and four of these were found to influence the adsorption of dye. A mathematical model equation was developed by using the CCD. Analysis of variance (ANOVA) indicated a high coefficient of determination (R2= 0.93). The initial dye concentration, amount of sesame stalk, contact time, and initial pH were shown to be very significant (p < 0.05) for RO4 adsorption. The data for the adsorption of RO4 at equilibrium on sesame stalk were analyzed by the Langmuir, Freundlich, and Tempkin models. Temperature increase from 20 to 60 °C enhanced the adsorption capacity of the monolayer from 84.75 to 178.57 mg/g. The rate constants were calculated for various initial concentrations of the dye by using pseudo-first and pseudo-second order kinetic and particle diffusion adsorption models. The kinetic evaluations showed that the experimental data were in accordance with the pseudo-second order model. © 2017 Technical University of Wroclaw. All rights reserved.
Keywords: Analysis of variance (ANOVA); Citrus fruits; Kinetics; Monolayers; Particle size; Particle size analysis; Rate constants; Adsorbent particle; Central composite designs; Contact time; Initial dye concentration; Initial pH; Model kinetics; Particles sizes; Placket-burman designs; Reactive Orange 4; Solution temperature; Adsorption